Metode Umat Wasatîyah dalam al-Qurâan (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
Interpretationâs study constantly faced with the difficulty of how to gain a thorough understanding (holistic) and avoid refractive understanding, the lack of continuity (matching) between the norms of Islam that is very noble to the reality of Muslim who are not âIslamicâ what causes that to happen? Is an understanding of aspects of Islam has ceased and focus on long heritage (turâth) this is no longer considered to be the actual state of time, or because the understanding of Islam was viewed as a textual only, so itâs resulting in an antagonistic attitude of Muslims and puritans! This article attempts to answer these questions.